Evaluation of Groundwater Quality Through Identification of Potential Contaminant - Sundarayamini, K.; Sivakumar, Vidhya Lakshmi; Balamurugan, P. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Groundwater, is crucial for human consumption and industrial purposes, demands continuous monitoring to assess quality standards. This study conducts a comprehensive evaluation of groundwater quality to assess its overall condition and identify potential contaminants. The research predicts the presence and levels of contaminants such as heavy metals, organic pollutants, and microbial agents using hydrogeological studies, chemical analysis, and statistical modelling. A covariance analysis identified places with low water quality.
Keywords: water quality evaluation; groundwater; water quality index (WQI); contaminants